PARADIGMA PENGEMBANGAN KURIKULUM PAI DI LEMBAGA PENDIDIKAN - Didiyanto Didiyanto (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2017)
The curriculum is a teaching and learning tool that needs to be developed in accordance with the existing developments in society. There are 3 kinds of paradigms in curriculum development, among others: 1. Diotomous paradigm, 2. Paradigm nikanisme, 3. Paradigm Organisem. Therefore, curriculum development is the process that determines how the curriculum will work. So in the preparation of curriculum development should consider the steps as follows: Formulation of Objectives; Define Content; Selecting Activities; And Formulate Evaluation. So in the preparation of curriculum development should consider the steps: 1) Formulation of Objectives, 2) Determining Content, 3) Selecting Activities, 4) Formulating Evaluation